Association of Comorbidities in Female Patients with Type 2 Diabetes Mellitus (Community Based Medical Journal, 2026)
Type 2 diabetes mellitus (T2DM) disproportionately affects women, with comorbidities exacerbating complications. Understanding their prevalence and patterns is crucial for effective management, especially in resource-constrained settings like Bangladesh, where gender-specific data remain scarce. A cross-sectional, observational study was conducted in the Department of Endocrinology, Mymensingh Medical College Hospital, Mymensingh, Bangladesh, between July 2021 and June 2022, to assess the prevalence and patterns of comorbidities among female type 2 diabetes mellitus patients, focusing on their association with demographic and clinical factors. A total of 110 females diagnosed with T2DM for ≤5 years, using oral anti-diabetic drugs (OADs) were included. Hospitalized patients, insulin users, and type 1 diabetes patients were excluded. Data was collected via patient interviews and prescription reviews. The mean age of the patients was 51.2±8.9 years. A high prevalence of comorbidities was observed: hypertension (64.5%), dyslipidemia (52.7%), obesity (17.3%), and hypothyroidism (13.6%). Patients ≥50 years had significantly higher hypertension (72.0% vs. 45.2%, p=0.002) and dyslipidemia rates (58.7% vs. 38.1%, p=0.013). Medication adherence was suboptimal in 42.7%, primarily due to cost (44.7%). Age ≥50 years (OR=2.0), rural residence (OR=1.6), and low education (OR=2.2), all of those factors significantly predicted comorbidities (p